FRUIT GROWING IN THE SOUTH-WEST OLTENIA REGION IN THE NATIONAL CONTEXT (2016-2022) - Andi CIOBANU; Dragoș Mihai MEDELETE; Radu Lucian PÂNZARU; Mihai CICHI (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper aims to anchor the fruit-growing heritage of the South-West Oltenia Development Region within the context of national realities. Thus, for the period 2016-2022, information is presented regarding the number of existing trees, total fruit production (tons), and average production per tree (kg). The general situation of the sector is addressed based on information related to the following species: plum, apple, pear, peach, nectarine, cherry, sour cherry, apricot, and other fruit trees – for the number of trees and average production per tree. Additionally, for these species, information on total production also includes strawberries and fruits from family gardens. This analysis is based on the main statistical database provided by the National Institute of Statistics. In terms of tree count, the region accounted for 18.03% of the national total, representing 13,501,467 trees. The variation ranges from 6.20% for nectarines (2,594 trees) to 34.66% for other fruit trees (469,931 trees).In the context of total national fruit production, the region accounted for 18.35% (277,886.57 out of 1,514,463.43 tons), with extreme shares of 6.59% for peaches (1,162.71 tons at the regional level compared to 17,633.86 tons at the national level) and 27.03% for other fruits (8,550.56 compared to 31,631.29 tons). The average production per tree (21 kg) places the region 5% above the national level (20 kg). There is a need for a significant revival of the fruit-growing sector, particularly through species that align with the agro-productive characteristics of the region, given adequate support from the authorized governmental bodies.